2020
DOI: 10.1088/2053-1591/ab8d5c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on structural, electronic, optical and mechanical properties of normal and high pressure phases titanium dioxide using DFT

Abstract: In this paper, a Self-consistent Orthogonalized linear combination of atomic orbitals (OLCAO) technique with a generalized gradient approximation such as Perdew-Burke-Ernzerhof Solid (GGA-PBE SOL) has been used to scrutinize the structural, optical, electronic and mechanical properties of normal pressure phase (Anatase and Rutile) and high pressure phase i.e., cubic (Fluorite and Pyrite) TiO 2 . Electronic and optical properties of normal pressure phases of TiO 2 are also investigated using (Meta) MGGA-Tran an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…The trend in the cell properties for a given correlated method with respect to the three PAW potentials is consistent with that observed for R-, A-, and B-TiO 2 (see above). We have observed that F- and P-TiO 2 lattices are relatively denser than that of the brookite, anatase, and rutile lattices of TiO 2 , in agreement with the computational data of Dharmale et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend in the cell properties for a given correlated method with respect to the three PAW potentials is consistent with that observed for R-, A-, and B-TiO 2 (see above). We have observed that F- and P-TiO 2 lattices are relatively denser than that of the brookite, anatase, and rutile lattices of TiO 2 , in agreement with the computational data of Dharmale et al…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have theoretically investigated the lattice properties, zone-center phonon vibrations, and the low- and high-frequency-dependent (ionic and electronic contributions, respectively) dielectric permittivity of rutile (R-)­TiO 2 using DFT at PBEsol and PBE , levels, with and without incorporating the Hubbard term U. , Density functional perturbation theory (DFPT) was employed for the evaluation of phonon vibrations and dielectric properties. The same properties were also investigated for the anatase and brookite phases, as well as for the two high-pressure structures of TiO 2 (called pyrite and fluorite ) for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that this discrepancy may be due to unphysical delocalisation of titanium's 3d electrons 21 , but it is not well-understood. Nevertheless, DFT, in particular using the PBEsol function, remains a useful tool for studying the high-pressure behavior [22][23][24] . It is also possible to overcome the incorrect ordering of phases using semi-empirical methods, such as DFT+U 25 and DFT+D 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, 15,16 and 17 reported high-pressure behavior of rutile. Theoretically, many researchers [18][19][20][21][22][23][24][25] did first-principle calculations on brookite and rutile TiO 2 without considering the pressure effect. Phase stability studies on various phases of TiO 2 are also published in the literature.…”
mentioning
confidence: 99%